(untitled) (Research, Society and Development, 2020)
A series of physiotherapeutic resources have been used in the rehabilitation of the upper limb after stroke, among them, the implementation of Functional Electrical Stimulation stands out. The purpose of the present study was to evaluate the effects of functional electrical stimulation on physiotherapeutic rehabilitation of the upper limb of post-stroke patients. It was made an systematic review of randomized clinical trials in the Science Direct, MEDLINE and PEDro databases. The methodological quality of the studies was assessed using the Physrootherapy Evidence Database (PEDro) scale. The results found showed that functional electrical stimulation is effective in improving motor function and decreasing tone, especially in wrist and hand joints. In addition, it can be used to prevent pain and subluxations in the shoulder and, when associated with the patient’s voluntary movement or intention, increases participation in activities of daily living and improves quality of life. The relevance of disclosing these findings lies in the fact that it reports the importance of using functional electrical stimulation in the rehabilitation of post-stroke patients conducted by the physiotherapist.